Ionic Interaction of MgSO4 with Mixed Organic Solvents - Junaid Mahmood, Syed; Azmat, Rafia; Uddin, Fahim; Taj, Noor (Asian Journal of Chemistry, 2010)
Densities and viscosities (η) of MgSO4 in formamide and ethylene glycol mixed solvents were measured at three different temperatures. The data was analyzed on the basis of Jones- Dole equation. Positive and increasing values of the B-coefficients show strong solute-solvent or ion-solvent interaction in the given mixed solvent system. Therefore, it may be concluded that the MgSO4 behaves as structure former or which enhances the structure of 48.32 % mole fraction of formamide + ethylene glycol solvent mixture. This study may be found true in measuring the transition state parameters. The values of free energy of activation of viscous flow of solution ΔU2º are greater than the values of free energy of activation of viscous flow of solvent system ΔU1º, which attributes that electrolyte i.e. magnesium sulphate is a structure enhancer or maker of the solvent system used in this study. Statistical calculations were also calculated as a function of salt's concentration and temperatures.